Utilization of Social Media in Building Personal Branding for Career Women in the Society 5.0 Era - Muhamad Bisri Mustofa; Fahrul Shiddiq; Khoirul Miftakhudin; Heni Rahmawati; Siti Wuryan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
The development of information technology in the digital era 4.0 continues towards the era of society 5.0, providing a variety of innovations and benefits for the community, especially career women. The social era of society 5.0 is a concept that defines technology and humans will coexist sustainably, improving the standard of living. However, limited people realize that social media can be used as a medium to create professional personal branding. This study aims to determine the use of social media in building personal branding for career women in the era of society 5.0. This research uses the Library Research Method and data collection based on previous research and journal. This study confirmed that Personal branding is crucial for self-promotion and support achievement for career women, specifically in the era of Society 5.0. The primary strategy to develop personal branding for career women is to utilize social media. Building strong personal branding on social media will make it easier for us to be known, both individually and in a professional scope. People can easily see our work, expertise, and achievements through social media that is automatically connected worldwide. 0 social media has a massive role in building someone's branding, including for a woman. Building strong personal branding on social media will make it easier for us to be known, both individually and in a professional scope. Social media lets people easily regard our work, expertise, and achievements worldwide.